Security - Dammert-Guardia, L (Taylor and Francis, 2020)
The challenges to security in the Americas are many. An increase in the use of violence and the regularization of organized crime are only some of the many facets to the problem in the region. In the past decades three changes in regard to crime stand out: (i) exportation of crimes; (ii) greater organization and complexity in criminal phenomena specially link to drug trafficking and (iii) difficulty for governmental institutions to address the problem. This situation has come hand in hand with substantial changes in the way in which public security is understood in the Americas - moving from a centralized vision focusing mainly on the role of criminal justice institutions in crime prevention toward a new, multidimensional approach that recognizes the importance of integral proposals for intervention. © 2020 selection and editorial matter, Olaf Kaltmeier, Anne Tittor, Daniel Hawkins and Eleonora Rohland; individual chapters, the contributors.